MgCr2O4 and MgCr2O4/Ag nanostructures: Facile size-controlled synthesis and their photocatalytic performance for destruction of organic contaminants‏. (15th October 2019) - Abbasi, Ali; Sajadi, Seyed Milad Safar; Amiri, Omid; Hamadanian, Masood; Moayedi, Hossein; Salavati-Niasari, Masoud; Beigi, Mahdi Mohammad
Abstract: The synthesized MgCr2 O4 nanoparticles were characterized by various techniques such as; XRD, SEM, EDS, TEM, DRS, TGA and IR. In order to improve the morphology of nanoparticles, several alkaline and capping agents were employed. In this manuscript TETA (full name), NH3 and N(Et)3 were used as alkaline agents and PVP, dimethylglyoxime (DMG) and 2-hydroxyacetophenone as capping agents. TETA and DMG were chosen as alkaline and stabilizer agents respectively that resulted in the spherical morphology of the MgCr2 O4 nanoparticles. Nanoparticles surface were covered by Ag nanoparticles using the photodeposition method. The photocatalytic behavior of MgCr2 O4 nanoparticles was evaluated using the demolition of several organic contaminates (rhodamine B, methylene blue and methyl orange) under UV irradiation. In order to investigate the photocatalytic properties of the nanoparticles, the effect of various type of pollutant, grain size and morphology of MgCr2 O4 nanostructures, various pollutants, dye dosage and pH of solution were studied on the photocatalytic behavior of products. Graphical abstract: Image 1 Highlights: MgCr2 O4 nanostructures were prepared by co-precipitation. The best morphology for MgCr2 O4 nanostructures were obtained by using DMG. Ag particles were deposited by photodeposition route on the surface of MgCr2 O4 nanoparticles. The photocatalytic activity of MgCr2 O4 and MgCr2 O4 /Ag nanostructures was tested.